Diagnostic accuracy of the defining characteristics of the excessive fluid volume diagnosis in hemodialysis patients - Maria Isabel da Conceição Dias Fernandes; Miclécia de Melo Bispo; Érida Maria Diniz Leite; Marcos Venícios de Oliveira Lopes; Viviane Martins da Silva; Ana Luisa Brandão de Carvalho Lira (Universidade de São Paulo, 2015)
Objective: to evaluate the accuracy of the defining characteristics of the excess fluid volume nursing diagnosis of NANDA International, in patients undergoing hemodialysis. Method: this was a study of diagnostic accuracy, with a cross-sectional design, performed in two stages. The first, involving 100 patients from a dialysis clinic and a university hospital in northeastern Brazil, investigated the presence and absence of the defining characteristics of excess fluid volume. In the second step, these characteristics were evaluated by diagnostic nurses, who judged the presence or absence of the diagnosis. To analyze the measures of accuracy, sensitivity, specificity, and positive and negative predictive values were calculated. Approval was given by the Research Ethics Committee under authorization No. 148.428. Results: the most sensitive indicator was edema and most specific were pulmonary congestion, adventitious breath sounds and restlessness. Conclusion: the more accurate defining characteristics, considered valid for the diagnostic inference of excess fluid volume in patients undergoing hemodialysis were edema, pulmonary congestion, adventitious breath sounds and restlessness. Thus, in the presence of these, the nurse may safely assume the presence of the diagnosis studied.